Bildungspraktiken der Aufklärung / Education practices of the Enlightenment. Journal für Kultur und Geschichte der Deutschen im östlichen Europa (JKGE) / Journal for Culture and History of the Germans in Eastern Europe - Pasewalck, Silke (De Gruyter, 2020)
This issue of JKGE is devoted to the specific conditions of educational processes in the pluri-cultural and multilingual regions of Eastern Europe. In the context of globally oriented research on the Enlightenment epoch, issues at the forefront include knowledge diffusion, translation, networking, interferences, asynchronicities, and ambivalences.